Exceptional dielectric properties of chlorine-doped graphene oxide/poly (vinylidene fluoride) nanocomposites. (August 2015) - Wu, Ying; Lin, Xiuyi; Shen, Xi; Sun, Xinying; Liu, Xu; Wang, Zhenyu; Kim, Jang-Kyo
Abstract: Herein, we report a facile method to significantly enhance the dielectric performance of reduced graphene oxide-based polymer composites. Addition of thionyl chloride into graphene oxide (GO) dispersion induces synergistic modifications of the structure, chemistry, charge carrier density and electrical conductivity of GO, as well as the interfacial interaction and phase of the surrounding matrix in the poly (vinylidene fluoride) (PVDF) composite. The composites reinforced with a very low reduced chlorinated GO (Cl-rGO) content of 0.2 vol% deliver an exceptional dielectric constant of 364 with a moderate dielectric loss of 0.077 at 1 kHz. These values are well contrasted with the corresponding properties of the neat PVDF polymer with a constant of 28 and a loss of 0.0029. Synergistic effects arising from chlorination are identified, including the much enhanced electrical conductivity of Cl-GO sheets by more than 3 orders of magnitude through introducing charge-transfer complexes, the improved interfacial interactions between the fillers and the PVDF matrix through hydrogen bonds, and the transformation of PVDF to β -phase with an inherently high dielectric constant due to dipolar interaction. The comparison with the literature data confirms superior dielectric performance of the present Cl-rGO/PVDF composites.